Androgen-Forming Stem Leydig cells: Identification, Function and Therapeutic Potential. Issue 4 (2008) - Zhang, Yunhui; Ge, Renshan; Hardy, Matthew P.
Abstract : Leydig cells are the primary source of testosterone in the male, and differentiation of Leydig cells in the testes is one of the primary events in the development of the male body and fertility. Stem Leydig cells (SLCs) exist in the testis throughout postnatal life, but a lack of cell surface markers previously hindered attempts to obtain purified SLC fractions. Once isolated, the properties of SLCs provide interesting clues for the ontogeny of these cells within the embryo. Moreover, the clinical potential of SLCs might be used to reverse age-related declines in testosterone levels in aging men, and stimulate reproductive function in hypogonadal males. This review focuses on the source, identification and outlook for therapeutic applications of SLCs. Separate pools of SLCs may give rise to fetal and adult generations of Leydig cell, which may account for their observed functional differences. These differences should in turn be taken into account when assessing the consequences of environmental pollutants such as the phthalate ester, diethylhexylphthalate (DEHP).